Outcome Assessment and Impact Estimation: FTA’s Research Contributions to Address the High Prevalence of Degraded Land and Ecosystem Services (Challenge 2) - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
Productive land sustains life, but the high prevalence of land and ecosystem service degradation poses a significant threat. The CGIAR’s Research Program on Forests, Trees, and Agroforestry (FTA) undertook research and engagement on various topics to address this key global challenge. The purpose of this report is to provide an account of FTA’s research, and the extent and nature of its contributions to outcomes and impacts on the restoration of degraded land and ecosystem services.